The Conceptual Framework of Natural and Social Science in Elementary School - Ahmad Irwan (Universitas Muhammadiyah Enrekang, 2020)
This conceptual framework of natural and social science in elementary school to study measures the relationship between innovative and loving organizational climate. Data was collected among Indonesian academics from state and private elementary school and analyzed using Smart PLSThe students' perceptions of effective interactive teaching using this technology were evaluated statistically using questionnaires. Based on data collected through participation in learning of natural and social science in elementary school. The findings reveal a significant positive relationship between the innovative organizational climate and organizational commitment of natural and social science in elementary school.